Los Pantanos de Villa Wildlife Refuge as a socioecosystem from a socioecological methodology - Arana Tejada, Lesly Llulina (2022)
The Pantanos de Villa Wildlife Refuge, recognized for its international importance or Ramsar Site, is a habitat for waterfowl, has biological, climatic and landscape values ​​and is in the urban area of ​​Metropolitan Lima. The socio-ecological system of the Pantanos de Villa is currently affected by anthropic factors such as urban expansion, the presence of industries, dumps, a fleet of vehicles, and others. In the present investigation, the Press-Pulse Dynamics model (pressure-pulse dynamics [DPP]) has been applied, which allows evaluations and comparisons of socio-ecological systems through the representation of existing links and feedbacks between the social and biophysical subsystems related with disturbances, whose consequences affect ecosystem services. As an external driver, urban growth has been identified, which is accompanied by pressures such as the change of land due to urban expansion, productive and commercial activities, the loss of biodiversity and the negligent disposal of solid waste, clearing and effluents, which has caused negative effects on ecological values, likewise, the social consequences affect the well-being of the social actors themselves, altering the ecosystem services they provide, which is why better management has to be carried out in order to recover and conserve the ecological habitat.